Preferred learning modalities and practice for critical skills: a global survey of paediatric emergency medicine clinicians. Issue 5 (16th October 2018) - Craig, Simon S; Auerbach, Marc; Cheek, John Alexander; Babl, Franz E; Oakley, Ed; Nguyen, Lucia; Rao, Arjun; Dalton, Sarah; Lyttle, Mark D; Mintegi, Santiago; Nagler, Joshua; Mistry, Rakesh D; et al.
Abstract : Objective: To describe senior paediatric emergency clinician perspectives on the optimal frequency of and preferred modalities for practising critical paediatric procedures. Methods: Multicentre multicountry cross-sectional survey of senior paediatric emergency clinicians working in 96 EDs affiliated with the Pediatric Emergency Research Network. Results: 1332/2446 (54%) clinicians provided information on suggested frequency of practice and preferred learning modalities for 18 critical procedures. Yearly practice was recommended for six procedures (bag valve mask ventilation, cardiopulmonary resuscitation (CPR), endotracheal intubation, laryngeal mask airway insertion, defibrillation/direct current (DC) cardioversion and intraosseous needle insertion) by at least 80% of respondents. 16 procedures were recommended for yearly practice by at least 50% of respondents. Two procedures (venous cutdown and ED thoracotomy) had yearly practice recommended by <40% of respondents. Simulation was the preferred learning modality for CPR, bag valve mask ventilation, DC cardioversion and transcutaneous pacing. Practice in alternative clinical settings (eg, the operating room) was the preferred learning modality for endotracheal intubation and laryngeal mask insertion. Use of models/mannequins for isolated procedural training was the preferred learning modality for all other invasive procedures. Free-text responses suggested the utility of cadaver labs and animal labs for more invasive procedures (thoracotomy, intercostal catheter insertion, open surgical airways, venous cutdown and pericardiocentesis). Conclusions: Paediatric ED clinicians suggest that most paediatric critical procedures should be practised at least annually. The preferred learning modality depends on the skill practised; alternative clinical settings are thought to be most useful for standard airway manoeuvres, while simulation-based experiential learning is applicable for most other procedures.